Research in goat productivity in tropical Africa - Lambourne, L.J. (Australian Centre for International Agricultural Research, 1985)
Reports research activities in goat productivity in tropical Africa. Discusses in detail the economic importance of goats; Development of breeds suited to various ecological zones; production systems and productivity & limitations; location & topics of current research activity, and present and future needs in goat research.